SHOCK CULTURE KOMUNIKASI ANTARBUDAYA SISWA LUAR DAERAH DI MADRASAH PENDHALUNGAN - Fasadena, Nova Saha; Jannah, Wardatul (International Conference on Humanity Education and Society (ICHES), 2024)
Culture Shock, or "gegar budaya," is a phenomenon that manifests in various new environments. This is no exception to what occurs at MA Al-Qodiri I Jember, where the Pendhalungan culture is practiced. Therefore, researchers are interested in examining the culture shock process experienced by students from outside the region at MA Al-Qodiri I Jember. Employing a qualitative approach, researchers observed, interviewed, and documented the culture shock processes among non-local students. The analysis was conducted through condensation and then verified by validating the data using triangulation of sources and techniques. The findings of the researchers indicate that language-induced culture shock, as a form of intercultural communication, can indeed pose challenges for new students. The primary obstacle faced by students from outside the region is encountering new terms or different names. However, the adaptation process, which typically takes less than a year, proves to be a viable solution for these students. Non-local students at MA Al-Qodiri primarily use Jemberan Madurese, Jemberan Javanese, or Jemberan Pendhalungan. The culture shock experienced by these students is not excessively high, resulting in a higher level of social adjustment.